Study Protocol of a Prospective Multicenter Study on Patient Participation for the Clinical Trial: Surgery as Needed Versus Surgery on Principle in Post-Neoadjuvant Complete Tumor Response of Esophageal Cancer (ESORES) - Weis, Joachim; Kiemen, Andrea; Schmoor, Claudia; Hipp, Julian; Czornik, Manuel; Reeh, Matthias; Grimminger, Peter P.; Bruns, Christiane; Hoeppner, Jens (Frontiers in Oncology, 2022)
Ideally, patient-centered trial information material encourages the discussion with the treating physician, and helps patients making trade-offs regarding treatment decisions In a situation of possible equivalent treatment options in terms of overall survival (OS), it can make it easier to weigh up advantages and disadvantages. Preferences for choice of treatment in esophageal cancer (EC) are complex, and no standardized assessment tools are available. We will explore patient’s factors for treatment choice and develop a comprehensive patient information leaflet for the inclusion into randomized controlled trials (RCT) on EC. We conduct a cross-sectional, observational study based on a mixed-methods design with patients suffering from non-metastatic EC with post-neoadjuvant complete response after neoadjuvant chemotherapy (nCT) or neoadjuvant chemoradiation (nCRT), to develop patient-centered trial information material. This pilot study is performed in a concept development phase and a subsequent pilot phase. We start with patient interviews (n = 10–15) in the concept development phase to evaluate patients’ needs, and develop a Preference and Decision Aid Questionnaire (PDAQ). We pre-test the PDAQ with another n = 10 patients with EC after nCT or nCRT, former patients from a self-help organization, and n = 10 medical experts for their comments on the questionnaire. In the pilot phase, a multicenter trial using the PDAQ and additional measures is carried out (n = 120). Based on evidence of a possible equivalence in terms of OS of the treatment options “surgery as needed” and “surgery on principle” in patients with post-neoadjuvant complete response of EC, this pilot study on patient participation is conducted to assess patient’s needs and preferences, and optimize patients’ inclusion in a planned RCT. The aim is to develop patient-centered trial information material for the RCT to increase patients’ consent and compliance with the randomized treatment. The trial is registered at the German Clinical Trials Register (DRKS00022050, October 15, 2020).